Increasing Gross Motor Skill Through Fundamental Skill Development Program - Sultoni, Kuston; Suherman, Adang; Wibowo, Ricky (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2018)
The aim of this study was to examine Canadian movement program called fundamental skill development programs implemented in Indonesia to increase children’s gross motor skills. By using a quasi-experiment, the matching-only pretest-posttest control group design, the sample was divided into two groups (N = 25 to the experimental group, N = 25 to the control group). The Gross motor skills were measured using the Test of Gross Motor Development - Second Edition TGMD - 2 Ulrich (2000). The experimental group was given training for eight weeks, 1 session per week and each session lasting 60 minutes. Statistical analysis was performed using paired sample t-test and independent sample t-test. The results showed that there is an increase in gross motor skills in the experimental group with P < 0.05. Then the results of independent sample t-test by comparing the Gain score between experimental group and the control group is significant difference with P < 0.05. It can be concluded that the fundamental skill development programs significant effect on gross motor skills in the first-grade student.